POLICY ON STRENGTHENING CHARACTER EDUCATION AT MADRASAH ALIYAH DARUL AMIN, KUTACANE, SOUTHEAST ACEH - Putri, Musdalipah; Hasmiani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
Character education is the main foundation in shaping the personality and morals of the younger generation in Indonesia. This study uses a qualitative descriptive method with field studies to understand and describe the process of character building at this madrasah. The research findings indicate that the implementation of Islamic religious education policies at MA Darul Amin plays a significant role in enhancing the students' religious character and noble morals. Programs such as daily worship routines, character education based on Islamic values, Islamic extracurricular activities, and an Islamic school environment contribute to the character formation of students. Strengthening the role of teachers as role models and collaboration with parents and the community are also key factors in the success of this program. This study found that Islamic religious education at MA Darul Amin not only enhances students' spirituality but also strengthens their social awareness. The implementation of this policy shapes students who not only excel academically but also possess good character and are ready to contribute positively to society. This research contributes to the development of Islamic religious education policies in Southeast Aceh and the improvement of the quality of education at MA Darul Amin Kutacane.